Monoamine oxidases as sources of oxidants in the heart - Kaludercic, Nina; Mialet-Perez, Jeanne; Paolocci, Nazareno; Parini, Angelo; Di Lisa, Fabio (Journal of molecular and cellular cardiology, 2014)
Oxidative stress can be generated at several sites within the mitochondria. Among these, monoamine oxidase (MAO) has been described as a prominent source. MAOs are mitochondrial flavoenzymes responsible for the oxidative deamination of catecholamines, serotonin and biogenic amines, and during this process they generate H2O2 and aldehyde intermediates. The role of MAO in cardiovascular pathophysiology has only recently gathered some attention since it has been demonstrated that both H2O2 and aldehydes may target mitochondrial function and consequently affect function and viability of the myocardium. In the present review, we will discuss the role of MAO in catecholamine and serotonin clearance and cycling in relation to cardiac structure and function. The relevant contribution of each MAO isoform (MAO-A or -B) will be discussed in relation to mitochondrial dysfunction and myocardial injury. Finally, we will examine both beneficial effects of their pharmacological or genetic inhibition along with potential adverse effects observed at baseline in MAO knockout mice, as well as the deleterious effects following their over-expression specifically at cardiomyocyte level. This article is part of a Special Issue entitled "Redox Signalling in the Cardiovascular System". •Monoamine oxidases are a major source of H2O2 within the mitochondria.•Their expression and activity is increased in several pathological conditions.•Monoamine oxidase inhibition prevents oxidative stress and cardiac dysfunction.•Monoamine oxidase-generated H2O2 and aldehydes can induce mitochondrial dysfunction.